European cardiac resynchronization therapy survey II: rationale and design - Dickstein, Kenneth; Normand, Camilla; Anker, Stefan; Auricchio, Angelo; Blomström, Carina Lundqvist; Bogale, Nigussie; Cleland, John; Filippatos, Gerasimos; Gasparini, Maurizio; Gitt, Anselm Kai; Hindricks, Gerhard; Kuck, Karl-Heinz; et al. (Europace, 2015)
The Cardiac Resynchronization Therapy (CRT) Survey II is a 6 months snapshot survey initiated by two ESC Associations,the European Heart Rhythm Association and the Heart Failure Association, which is designed to describe clinical practiceregarding implantation of CRT devices in a broad sample of hospitals in 47 ESC member countries. The large volume ofclinical and demographic data collected should reflect current patient selection, implantation, and follow-up practice andprovide information relevant for assessing healthcare resource utilization in connection with CRT. The findings of thissurvey should permit representative benchmarking both nationally and internationally across Europe.
Online publish-ahead-of-print 17 November 2014